Prensa, actualidad política y romanticismo español : el caso de J. Morán y la corte de Juan II de Castilla - Montserrat Ribao Pereira (Amnis)
Throughout the 19th century references to the complex court of King Juan de Castilla were common in the Spanish press. Thus, articles, stories, poems and legends published in the papers of the age invoke the 15th century through Romanticized descriptions of the conflicts affecting the nation at the time. This article focuses on the particular case of Jerónimo Morán and Don Álvaro de Luna as examples par excellence of the above.